Using validated assessment tools in stoma care: a case study of an ileostomate with an inward body profile. (2nd March 2021) - Russell-Roberts, Paul; Kay, Diane
Abstract : The impact of having a stoma on an individual's quality of life (QoL) can be significantly worsened by leakage and consequent peristomal skin complications. Therefore, ostomates require individualised, person-centred and evidence-based care. Stoma care nurses can facilitate this using stoma-specific validated assessment tools, including the Body Profile Assessment Tool, Stoma Quality of Life Tool, Ostomy Skin Tool and Ostomy Leakage Impact Tool. These provide precise, repeatable quantitative data, which avoids reliance on vague language and allows for baseline comparisons to measure progression. This case study describes a female ileostomate who faced a number of stoma-related complications, including body image and confidence. Initial trial-and-error attempts to find an effective combination of products were fragmentary and failed to provide an effective long-term solution. During the COVID-19 pandemic, the patient underwent a remote telephone consultation, aided by digital photography. The stoma care nurse used validated assessment tools to determine the patient's needs. Based on this, she was recommended a new pouching routine suited to her inward body profile, and her progress was measured using the assessment tools. These showed sustained and considerable improvements in peristomal skin health, mental wellbeing and overall QoL. The patient's prescription costs were also dramatically reduced.